A review on emissions reduction techniques used in internal combustion engines. (5th August 2021) - Singh, Digambar; Sharma, Dilip; Soni, S.L.; Sharma, Sumit; Sharma, Pushpendra Kumar; Jhalani, Amit
Continuous growing population and a rise in living standards are creating widespread use of vehicles. Motor vehicle emissions contribute significantly to air pollution and other adverse environmental and health effects. The primary contaminants from internal combustion (IC) engines are NOx, CO, CO2, unburnt hydrocarbons (HC), and PM. Their control strategies were considered seriously throughout the discussion. This analysis summarises emissions from both compression ignition (CI) and spark ignition (SI) engines with government-setting emission regulatory standards. This article also gives detailed insight into pollution monitoring methods and their control policy for both CI and SI engines. Emissions from SI engines are more harmful to human health, with more CO and HC emissions in comparison with CI engines. CO emissions are insignificant in CI engines due to lean-burn nature. High temperatures and significant oxygen supply in the combustion chamber make CI engines prone to NOx emissions. This analysis will help researchers to obtain comprehensive emission and their reduction methodologies information for IC engines.